Survival of Patients With Non‐Rhabdomyosarcoma Soft Tissue Sarcomas of the Head and Neck. (12th June 2020) - Rastatter, Jeffrey C.; Sinard, Rebecca N.; Dilger, Amanda; Reichek, Jennifer; Walterhouse, David O.; Patel, Urjeet
Abstract : Objective: To evaluate factors associated with overall survival (OS) of patients with non‐rhabdomyosarcoma soft tissue sarcomas of the head and neck. Study Design: Retrospective cohort study. Methods: The National Cancer Database was queried for cases of non‐rhabdomyosarcoma soft tissue sarcomas of the head and neck between 2004 and 2014. Cases were categorized according to the World Health Organization classification of soft tissue tumors. A multivariable Cox proportional hazards model was used to evaluate associations with OS. Results: A total of 4, 555 patients (63.6% male, 36.4% female, mean age 59.6 years) met inclusion criteria. The majority of tumors were classified as miscellaneous (35.9%), followed by vascular (20.1%), smooth muscle (13.5%), fibroblastic/myofibroblastic (12.1%), peripheral nerve (8.5%), adipocytic (7.4%), and undifferentiated (2.5%) sarcomas. The mean follow‐up was 37.9 months, and overall mortality (MR) was 45.3%. The best prognosis was seen with fibroblastic/myofibroblastic sarcomas (MR = 20.6%, P  < .001), whereas vascular sarcomas had the worst prognosis (MR = 67.6%, P  < .001). Resection with clear margins had better OS than microscopically positive margins (hazard ratio [HR] = 1.43, P  < .001) or grossly positive margins (HR = 2.97, P  < .001). Radiation therapy was associated with better OS than no radiation (HR = 0.86, P = .001). Conclusion: Non‐rhabdomyosarcoma soft tissue sarcomas of the head and neck are associated with significant mortality. OS differs based on histologic subcategorization. Resection of the primary tumor with clear margins demonstrates improved OS for all histologies, suggesting this modality remains the preferred primary treatment when feasible. Level of Evidence: 3 Laryngoscope, 131:E500–E508, 2021